Analyzing Emotions in Students' Response Poems to Kitty O' Meara's (2020) "And the People Stayed Home": A Reader-Response Study - Syifa Arsyana Sabila, - (2021)
In literary works, poetry is considered a powerful tool in conveying and awakening emotions for both the writer and the reader. Poetry, oftentimes, reflect the innermost thoughts of the writer and the world in which she or he lives. Writing and reading a poem engage with human senses, creating a connection between the writer, the reader, and the text. Drawing from Rosenblatt's (1982) reader-response theory, this study aims to explore and understand how emotions are presented in poems through the analysis of tone, mood, and figurative language of the poems. The poems used are taken from fifteen first-semester students' response poems of Kitty O'Meara's (2020) "And the People Stayed Home", which talks about the pandemic the students are going through. This study shows that the students express a vast range of emotions, such as anger, denial, acceptance, and happiness in relation to the COVID-19 issue brought up in O'Meara's poem. As proposed by Rosenblatt, a more self-critical interpretation is developed through the students' ability in connecting, reasoning, and creating the meaning of the text. The study confirms that the reader-response approach provides a space for students to be more engaged, open, and creative in their interpretations of the text.